Well-being and happiness: A study of panel data in the municipality of Pasto, Colombia during 2008-2010 - Ortiz Benavides, Edinson (Universidad y Salud, 2016)
Introduction: The pursuit of happiness is an end of society, where sometimes being wealthier, having more income and more goods lead effectively to it. Objective: To establish the relationship between happiness and welfare in subjective terms. Materials and methods: A Logit Binomial econometric model was applied to the Panel data from the survey previously applied to 4.797 individuals and 1,123 households in the municipality of Pasto, Colombia during the years 2008-2010. Results: Statistically significant, people who manifest a better condition of welfare state declared themselves to be 13% happier than those who do not. Conclusion: The study allows to conclude that this model finds the relationship between happiness and welfare in the municipality of Pasto, Colombia for the study period. It confirms that people with higher levels of welfare are declared to be happier than those who, according to their own evaluation, have not been.